O predvidljivosti in nepredvidljivosti v razvoju kulture - Javornik, Miha (Slavistična revija, 2002)
The paper considers the development of culture and, in so doing, gives particular attention to contemporary communicative and cultural modes that are brought by the digitalization of information. The analysis indicate that we are dealing with a repetition of the processes that in history build the property of cultural development. The question in posed about the realitonship between regularity and chance when the interaction between the two results in evolution.
Keywords: culture; internet; kultura; semiotics; semiotika